The Influence of Clinical Competence and Work Motivation on General Practitioners’ Performance at National Cancer Centre Hospital: a cross-sectional study - Sari, Resti Mulya; Pamungkas, Rian Adi; Wahidi, Kemala Rita (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: General practitioners are responsible for providing health services, such as disease prevention, diagnosis, initial treatment, and referring patients to specialists based on the severity of the disease. Objective: This study aims to determine the influence of clinical competence and work motivation on the performance of general practitioners, with training serving as an intervening variable. Methods: This study was conducted at National Cancer Centre Hospital in January-June 2022. This is a cross-sectional study with a path analysis as its analysis method. The respondents were general practitioners who provide services to patients, with a total respondent of 51 participants. Result: This study reported an influence of simultaneous clinical competence and work motivation on general practitioners' working performance with training as an intervening variable (p=0.000). According to the partial test result, there was an effect of clinical competence on general practitioners' performance (p=0.000) and an effect of training on general practitioners' performance (p=0.003). There was no effect of work motivation on general practitioners' performance (p=0.302) or training (p=0.555). Conclusion: There is a simultaneous influence of clinical competence and work motivation on the performance of general practitioners, with training as an intervening variable. The study results suggest creating specific standards of competence for general practitioners working at the National Cancer Centre. Furthermore, it is necessary to hold training for general practitioners in accordance with the particular competencies needed to improve and maintain.